School Integration of Refugee Children: Evidence from the Largest Refugee Group in Any Country - Murat G. Kirdar; Ismet Koc; Meltem Dayioglu-Tayfur (Institute of Labor Economics (IZA), 2021)
Although school integration of the children of economic migrants in developed countries is well-studied in the literature, little evidence based on large scale representative data exists on the school integration of refugee children—many of whom live in low- or middle-income countries. This study focuses on Syrian refugee children in Turkey and examines the underlying causes of the native-refugee differences in school enrollment. We also analyze employment and marriage outcomes, as they are potentially jointly determined with schooling. For this purpose, we use the 2018 Turkish Demographic and Health Survey, which includes a representative sample of Syrian refugee households. We find that once a rich set of socioeconomic variables are accounted for, the native-refugee gap in school enrollment drops by half for boys and two-thirds for girls, but the gap persists for both genders. However, once we restrict the sample to refugees who arrive in Turkey at or before age 8 and account for the socioeconomic differences, the native-refugee gap completely vanishes both for boys and girls. In one outcome—in never attending school—the native-refugee gap persists even for children who arrive before age 8. Data for Syrians from the pre-war period suggest that this might be an "ethnic capital" that they bring with them from Syria. Finally, we find that the timing of boys' school drop-out coincides with their entry into the labor market, whereas girls' drop-out mostly takes place earlier than their marriage.
Keywords: F22; I21; I28; O15; 330; refugees; education; school enrollment; integration; child labor; marriage; Turkey